Non-custodial sentences in the Northern Areas: Female offenders’ experience - Thornton, Jessica (Technium Social Sciences Journal, 2022)
While studies on female offenders in South Africa are valuable, very few have provided an understanding of women serving alternative sentences. This is critical in South Africa considering its slow administration of justice and the use of ‘alternative’ sentencing could possibly relieve the conditions in correctional centres. Since alternative sentencing is less retributive than incarceration, they are assumed to be more restorative in reforming and reintegration. However, when the offenders are placed back into the society that promoted the criminal behaviour, it becomes difficult to govern. This ethnographic study explores the lived experiences of five female offenders serving non-custodial sentences in Port Elizabeth’s Northern Areas, a known gang area.